2020
DOI: 10.34119/bjhrv3n6-112
|View full text |Cite
|
Sign up to set email alerts
|

Facilitators and obstacles to implementing the practical approach to the care kit/pack Brazil / Facilitadores e obstáculos para implementar a abordagem prática do kit de cuidados/ pacote Brasil

Abstract: Facilitators and obstacles to implementing the practical approach to the care kit/pack Brazil Facilitadores e obstáculos para implementar a abordagem prática do kit de cuidados/ pacote Brasil

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Another study identified that PHC nurses from Florianópolis prefer to use Nursing protocols as a basis for carrying out their clinical practices, as they understand that they are frequently updated and guarantee greater legal support for their work (19) . The PACK's clinical guidelines are conceptually aligned and updated with the municipal protocols, therefore, they constitute important technologies that guide the care of this health condition.…”
Section: Discussionmentioning
confidence: 99%
“…Another study identified that PHC nurses from Florianópolis prefer to use Nursing protocols as a basis for carrying out their clinical practices, as they understand that they are frequently updated and guarantee greater legal support for their work (19) . The PACK's clinical guidelines are conceptually aligned and updated with the municipal protocols, therefore, they constitute important technologies that guide the care of this health condition.…”
Section: Discussionmentioning
confidence: 99%